The Role of Resilience in Minimizing Conditions of Learned Helplessness in Undergraduate Students at Universitas Negeri Malang - Putri, Raissa Dwifandra; Farida, Ika Andarini; Masfufah, Ulfa; Widyatno, Aryudho; Rahmawati, Yuliana Mukti (Jurnal Sains Psikologi, 2023)
The condition of learned helplessness is a condition that is vulnerable to undergraduate students. Various conditions of learned helplessness in students can be caused by changes in the environment, daily activities, and even academic challenges. Furthermore, this condition can impact a state of depression and even suicidal ideation in students. Various efforts are made to minimize or inhibit the negative impact of learned helplessness conditions by students through strengthening internal strengths within individuals, such as resilience. This research was conducted to see the role of resilience in minimizing conditions of learned helplessness among undergraduate students at Universitas Negeri Malang. This research is quantitative research with a correlational research design. Participants in this research were active undergraduate students at Universitas Negeri Malang. The instrument used to measure learned helplessness is the Learned Helplessness Scale (LHS) and the Adult Resilience Measurement Revised (ARM-R) for resilience. Both of them were adapted into Indonesian. The total participants involved in this research were 85 students from 8 faculties (M is equal to 19.99 ± 1.66). The results of the research show that there is a role of resilience in the condition of learned helplessness among undergraduate students of Universitas Negeri Malang, which is 23 percent.